DETERMINATION OF THE CONTENT OF CHEMICAL ELEMENTS IN THE "ASFAM" FOOD ADDITIVE (Scientific journal of the Fergana State University, 2026)
In experiments conducted using the ICP-OES method, the analysis of the food additive “Asfam,” which is composed of mandarin and kiwi fruit peels, enabled the accurate quantification of 39 out of 69 chemical elements. The results showed that this food additive is rich in essential macroelements such as K, Ca, Mg, P, and Na, as well as biogenic microelements including Sn, Fe, Al, Sr, Si, Mn, Ba, Zn, B, Cr, Cu, Ni, Li, and Mo. It was proven that the levels of heavy metals and the toxic element arsenic in the “Asfam” food additive are significantly lower than the permissible limits.c